Implementation of Heritage Distribution in the Community in Islamic Law Antropology Perspective (Study On Simalungun Tribe In Kuta Baru Village, Tebing Tinggi, Serdang Bedagai Regency) - Muhammad Zuhirsyan; Maswandi Maswandi; Jamillah Jamillah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to discuss implementation of heritage distribution in the community in Islamic law antropology perspective (study on Simalungun tribe in Kuta Baru Village, Tebing Tinggi, Serdang Bedagai Regency). As for the object of the same study of Simalungun tribe has not been found. One of the Muslim communities of the Simalungun tribe found in Kuta Baru Village, Tebing Tinggi Sub-District, Serdang Bedagai Regency, North Sumatra. The result shows that there are several forms of the implementation of the distribution of inheritance by the Simalungun Muslim population. Among them is to divide based on the provisions that have been made by their parents during his lifetime. There are also those who divide according to Islamic law through a division that only considers the male portion is twice as large as girls. It was also found that the distribution of the inheritance was not carried out and the management of the land according to the level of needs of each of them.